The Development of Arabic and Islamic Education During the Mataram Sultanate (Sultan Agung's Era 1613-1645) - Fauzan Nurfalah; Supianudin, Asep (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
Arabic and Islamic education played a pivotal role in the Mataram Sultanate, particularly during the reign of Sultan Agung Hanyakrakusuma and that time was tha greatest era of Mataram Sultanate. So, that time was the best islamic and arabic education system that time. His work Sastra Gendhing exemplifies the integration of Arabic linguistic elements and Islamic values into Javanese culture. This study aims to trace the historical presence and influence of Arabic language and Islamic education in Java during Sultan Agung’s administration. Employing a literature review method, the research examines historical texts and references related to the educational practices of the period. Findings reveal that Arabic and Islamic teachings were disseminated through kitab kuning (classical Islamic texts, kutub turâts), a pedagogical approach still prevalent in contemporary Islamic boarding schools. The study concludes that the Mataram Sultanate laid a foundational role in embedding Arabic and Islamic education into Javanese society, leaving a lasting legacy that continues to shape religious and linguistic traditions in the region.